2020
DOI: 10.1073/pnas.2004489117
|View full text |Cite
|
Sign up to set email alerts
|

B cells expressing authentic naive human VRC01-class BCRs can be recruited to germinal centers and affinity mature in multiple independent mouse models

Abstract: Animal models of human antigen-specific B cell receptors (BCRs) generally depend on “inferred germline” sequences, and thus their relationship to authentic naive human B cell BCR sequences and affinities is unclear. Here, BCR sequences from authentic naive human VRC01-class B cells from healthy human donors were selected for the generation of three BCR knockin mice. The BCRs span the physiological range of affinities found in humans, and use three different light chains (VK3-20, VK1-5, and VK1-33) found among … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
58
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 61 publications
(175 reference statements)
2
58
1
Order By: Relevance
“…Allelic inclusion. To assess the surface expression of endogenous LCs in engineered VRC01+ cells, B cells from knock-in mice expressing LCs with only human κ constant chains33 were purified, activated, and engineered using the H-targeting strategy. Fc Blocker (homemade mAb 2.4g2) was added to single-cell suspensions at 0.5 mg per 10 6 cells before antibody staining.…”
mentioning
confidence: 99%
“…Allelic inclusion. To assess the surface expression of endogenous LCs in engineered VRC01+ cells, B cells from knock-in mice expressing LCs with only human κ constant chains33 were purified, activated, and engineered using the H-targeting strategy. Fc Blocker (homemade mAb 2.4g2) was added to single-cell suspensions at 0.5 mg per 10 6 cells before antibody staining.…”
mentioning
confidence: 99%
“…It is possible that these off-target B cell responses will be recalled and predominate the B cell responses upon subsequent Env immunizations. In line with this, adoptive transfer experiments where B cells expressing putative VRC01 precursors or intermediates with defined B cell receptor (BCR) specificity are introduced into a wild-type (WT) mouse at a controlled frequency demonstrated that immunogens with high affinity and/or avidity for the target BCR were required for successful inter-clonal competition of rare target B cells following a priming immunization (Dosenovic et al, 2018;Abbott et al, 2018;Huang et al, 2020;Kato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Defined as the tendency of the immune system to respond to complex antigens in a hierarchical manner, the immunodominance patterns enforced following influenza infection and vaccination prioritize the expansion of non-neutralizing antibodies against ‘off-target’ hypervariable features at the expense of ‘on-target’ responses engaging functionally conserved epitopes [ 1 , 78 , 79 , 80 , 81 , 82 , 83 ] ( Figure 2 ). Structure-based influenza immunogens applied within transgenic mouse systems bearing user-defined B cell receptor (BCR) repertoires, along with similar approaches using HIV antigens, have enabled experimental manipulation of these parameters [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. This work indicates that the immunogenicity of a given epitope is a function of the frequency and affinity of the on-target versus off-target BCRs present in the antigen naïve germline repertoire.…”
Section: Subverting Natural Immunodominance Hierarchies: An Immunomentioning
confidence: 99%
“…This work indicates that the immunogenicity of a given epitope is a function of the frequency and affinity of the on-target versus off-target BCRs present in the antigen naïve germline repertoire. Subdominant antibody responses thus arise when low frequency and/or low affinity on-target BCRs are unable to compete for expansion within B cell germinal centers (GCs), allowing off-target (‘immuno-distracted’) B cells to then dominate the GC reaction [ 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Such off-target anti-influenza BCRs proceed to overshadow antibody affinity maturation, the downstream serum antibody response, and the development of B cell memory [ 85 , 86 ].…”
Section: Subverting Natural Immunodominance Hierarchies: An Immunomentioning
confidence: 99%